2003
DOI: 10.1002/erv.518
|View full text |Cite
|
Sign up to set email alerts
|

The use of palmtop computers in the treatment of bulimia nervosa

Abstract: Palmtop computers may provide an innovative and effective extension of psychotherapeutic treatment for eating disorders. Palmtop applications have been used historically in studies utilizing ecological momentary assessment methodology, and in this capacity their portability and immediacy have been advantageous. In this paper, a new treatment for bulimia nervosa will be described which includes palmtop modules as therapy extension devices. The format of the therapy will be reviewed along with the specific conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 29 publications
0
18
0
3
Order By: Relevance
“…For example, pre-and post-treatment EMA measures could be obtained to assess how the antecedents and consequences of binge episodes change following intervention. Another future research direction is the use of EMA, such as the keypads used in the present study, as an intervention in itself or as an added component to intervention (e.g., as has been done for BN 41 ). This may be especially promising given the data that binge eaters find similar timerprompted self-monitoring to be relatively helpful, 25 and in light of the increasing prevalence and sophistication of computer and handheld technology.…”
Section: Resultsmentioning
confidence: 98%
“…For example, pre-and post-treatment EMA measures could be obtained to assess how the antecedents and consequences of binge episodes change following intervention. Another future research direction is the use of EMA, such as the keypads used in the present study, as an intervention in itself or as an added component to intervention (e.g., as has been done for BN 41 ). This may be especially promising given the data that binge eaters find similar timerprompted self-monitoring to be relatively helpful, 25 and in light of the increasing prevalence and sophistication of computer and handheld technology.…”
Section: Resultsmentioning
confidence: 98%
“…Because electronic diaries are so ubiquitous, they may provide a convenient, accessible, and nonthreatening modality for recording behaviors, emotions, and cognitions in public situations. ESMDs can also be used as an adjunct to clinician guidance by reminding patients to complete homework assignments and providing coping strategies and psychoeducation that can be used during times of crisis or distress (Norton, Wonderlich, Myers, Mitchell, & Crosby, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…One study, which used PDAs as an extension to therapy, reported that signals from the device reminded clients to think about things like eating behaviour and mood (Norton, Wonderlich, Myers, Mitchell, & Crosby, 2003).…”
Section: Mobile Software To Support Psychotherapymentioning
confidence: 99%